Response of two different Phoenix dactylifera cultivars to future climate conditions - Kaabi, Nasser Abdullah Ghdayer Al; Blooshi, Saif Ali Matar Al; Kandhan, Karthishwaran; Jaleel, Abdul; Alyafei, Mohammed Abdul Mohsen (Journal of Aridland Agriculture, 2023)
Plants are naturally exposed to various environmental stresses that affect their growth and development. As a desert plant, Phoenix dactylifera (date palm) has developed strategies to protect itself from most abiotic stresses. However, projected climate changes and the interaction between the various abiotic stressors will have profound effects on date palm adaptation and production In the present study, the two date palm cultivars, Sultana and Zamli cultivars were exposed to elevated levels of CO2 and enhanced UVB radiation and non-enzymatic antioxidants (total phenols, α-tocopherol, reduced glutathione content) and antioxidant enzyme activities (polyphenol oxidase, peroxidase, superoxide dismutase, catalase, ascorbate peroxidase) activities were analysed. The results showed that the Sultana cultivar is tolerant to future climate conditions. However, more biotic stress and yield parameters are needed for the identification of biotic stress tolerant date palm cultivars.